The derivative of [tex]f(x) = 2\cdot x^{2}-9[/tex] is [tex]f'(x) = 4\cdot x[/tex].
In this exercise we must apply the definition of derivative, which is described below:
[tex]f'(x) = \lim_{x \to 0} a_n \frac{f(x+h)-f(x)}{h}[/tex] (1)
If we know that [tex]f(x) = 2\cdot x^{2}-9[/tex], then the derivative of the expression is:
[tex]f'(x) = \lim_{h \to 0} \frac{2\cdot (x+h)^{2}-9-2\cdot x^{2}+9}{h}[/tex]
[tex]f'(x) = 2\cdot \lim_{h \to 0} \frac{x^{2}+2\cdot h\cdot x + h^{2}-2\cdot x^{2}}{h}[/tex]
[tex]f'(x) = 2\cdot \lim_{h \to 0} 2\cdot x + h[/tex]
[tex]f'(x) = 4\cdot x[/tex]
The derivative of [tex]f(x) = 2\cdot x^{2}-9[/tex] is [tex]f'(x) = 4\cdot x[/tex].
We kindly invite to check this question on derivatives: https://brainly.com/question/23847661